Influence of CuO Addition on the Structural, Magnetic and Electrical Properties of Nd0.67Sr0.33MnO3 Composites - Lau, L. N; Hon, X.T; Lim, K. P; Mazlan, N. A; Kechik, M. M. Awang; Chen, S. K; Shabdin, M. K; Shaari, A. H (Balai Publikasi Indonesia, 2025)
Colossal magnetoresistance (CMR) materials are widely studied to be applied in magnetic sensing elements. The incorporation of a secondary oxide phase into manganites has been explored to improve low-field magnetoresistance (LFMR). In this study, polycrystalline Nd0.67Sr0.33MnO3 (NSMO) was synthesised via the sol-gel method, and different contents of CuO nanopowder were added to form (1–x) NSMO: x CuO composites. The structural, magnetic, and electrical properties of the composites were characterised by X-ray diffraction (XRD), AC susceptibility (ACS), and Hall effect measurement (HMS). XRD results confirmed the orthorhombic structure in all samples and indicated no reaction between NSMO and CuO, suggesting that CuO segregates at the grain boundaries or surfaces of NSMO grains. Magnetic measurements revealed negligible variation in the Curie temperature (TC), while electrical measurements showed a suppression of the metal–insulator transition temperature (TMI). Although LFMR was more pronounced at lower temperatures, no enhancement was observed in the NSMO composites compared to its parent compound. This behaviour is attributed to spin-polarised tunnelling, which dominates LFMR and is primarily dominated by the nanoscale NSMO achieved through sol-gel synthesis. These findings offer valuable insights into the magnetotransport properties of NSMO:CuO composites and the role of secondary oxide phases in tailoring LFMR.